2016
DOI: 10.1186/s12878-016-0057-5
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic predictive value of platelet indices for discriminating hypo productive versus immune thrombocytopenia purpura in patients attending a tertiary care teaching hospital in Addis Ababa, Ethiopia

Abstract: BackgroundBone marrow examination may be required to discriminate causes of thrombocytopenia as hypoproductive or hyperdestructive. However, this procedure is invasive and time consuming. This study assessed the diagnostic value of Mean Platelet Volume (MPV), Platelet Distribution Width (PDW) and Platelet Large Cell-Ratio (P-LCR) in discriminating causes of thrombocytopenia as hypoproductive or hyperdestructive (Immune thrombocytopenia purpura).MethodA prospective cross-sectional study was conducted on 83 thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 24 publications
4
38
1
2
Order By: Relevance
“…[15] ;Negash et al [16] who found that the MPV is significantly elevated in ITP patients than in patients with hypoproductive thrombocytopenia. In disagreement with this result, a study conducted by Borkataky et al [17] who found no significant difference in the MPV between the destructive thrombocytopenia groups and the control group.…”
mentioning
confidence: 99%
“…[15] ;Negash et al [16] who found that the MPV is significantly elevated in ITP patients than in patients with hypoproductive thrombocytopenia. In disagreement with this result, a study conducted by Borkataky et al [17] who found no significant difference in the MPV between the destructive thrombocytopenia groups and the control group.…”
mentioning
confidence: 99%
“…A few previous studies have investigated the relationship between the MPV and ITP. MPV was found higher in ITP than aplastic anaemia [3], chemotherapyrelated myelosuppression [4], myelodysplastic syndrome [8] and other hypoproductive thrombocytopenia [6]. MPV was also found higher in ITP than healthy controls [6,12].…”
Section: Discussionmentioning
confidence: 86%
“…So, it is assumed that MPV is high in the ITP patients. The previous studies indicated that MPV may be used to differentiate between hypo and hyper productive thrombocytopenia and ITP patients have higher MPV than the hypoproductive thrombocytopenia (aplastic anaemia, myelodysplasia) [3][4][5][6][7][8]. However, different mechanisms may be dominant in different patients and this may cause different MPV values in patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations